Drawing on/from a mirror : a self-reflexive study of the representation and perception of violence in contemporary film - Marnewick, Benjamin Meiring (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2011.